Physical, structural, and water barrier properties of emulsified blend film based on konjac glucomannan/agar/gum Arabic incorporating virgin coconut oil. (15th January 2022) - Xiao, Man; Luo, Ling; Tang, Bin; Qin, Jiaming; Wu, Kao; Jiang, Fatang
Abstract: This study aimed to develop a new emulsified film based on konjac glucomannan (KGM)/agar/gum Arabic (GA) incorporating virgin coconut oil (VCO). The effects of VCO on the physical, structural, and water barrier properties of the film were investigated. The values of the mechanical and water barrier properties were different with statistical significance (p < 0.05), with VCO contents ranging from 0.1% to 0.6% of the film solid weights. The addition of VCO decreased the tensile strength but effectively increased the elongation at the break of the films. Increased VCO concentrations resulted in decreased water vapor permeability, reduced water swelling, solubility, and adsorption, and increased water contact angle. Compared with cucumber without packaging, packed cucumber with emulsified film showed significantly lower weight loss and firmness reduction during storage up to 12 days at 7 ± 1 °C. Fourier transform infrared spectroscopy results indicated intermolecular hydrogen bonds between KGM, agar, and GA occurred, and X-ray diffraction results suggested that all the films were in the amorphous status. Combining all the above results, the mechanism of the water barrier property improvement was proposed. This study offers an alternative emulsion polysaccharide-based edible film with high potential to be used in cucumber packaging. Graphical abstract: Image 1 Highlights: A novel konjac glucomannan-based emulsified film was fabricated and characterized. Virgin coconut oil addition greatly improved the water barrier property of the film. Virgin coconut oil addition can positively influence the EAB of the film. Effect of emulsified film was assessed on the preservation of cucumber.